Purpuric pityriasis rosea in patients with anorexia nervosa (Dermatology Reports, 2025)
Pityriasis rosea (PR) is an exanthematous disease associated with the endogenous systemic reactivation of human herpesvirus (HHV)-6 and/or HHV-7. Variants of PR characterized by atypical lesion morphology, eruption course, and severe symptoms have already been described, but their prevalence is probably underestimated. We report herein two patients suffering from anorexia nervosa (AN) who developed a very rare form of purpuric PR. So far, no cases of PR in AN patients have been reported in the literature. In AN, impaired cell-mediated immunity may favor the endogenous systemic reactivation of HHV- 6 and/or HHV-7, causing PR. Furthermore, an increased level of the vascular cell adhesion molecule 1, interleukin 6, and tumor necrosis factor-α has been demonstrated in AN patients, which may be responsible for their increased vascular dysfunction.